2021
DOI: 10.1111/febs.15751
|View full text |Cite
|
Sign up to set email alerts
|

Jazf1 acts as a regulator of insulin‐producing β‐cell differentiation in induced pluripotent stem cells and glucose homeostasis in mice

Abstract: Genetic susceptibility of type 2 diabetes and Juxtaposed with another zinc finger protein 1 (Jazf1) has been reported; however, the precise role of Jazf1 in metabolic processes remains elusive. In this study, using Jazf1knockout (KO)-induced pluripotent stem cells (iPSC), pancreatic beta cell line MIN6 cells, and Jazf-1 heterozygous KO (Jazf1 +/À ) mice, the effect of Jazf1 on gradual differentiation was investigated. We checked the alterations of the genes related with b-cell specification, maturation, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Tr4 KO mice showed low IGF-1 serum concentrations and early growth retardation ( 27 ), similar to what we observed in Jazf1 KO mice. A recent study showed decreased GSIS in beta cell-specific Jazf1 KO mice under hyperglycemic condition ( 16 ) and in beta cells differentiated from Jazf1 KO ( 17 ). Thus, we tested whether TR4 expression or insulin secretion was affected in our animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tr4 KO mice showed low IGF-1 serum concentrations and early growth retardation ( 27 ), similar to what we observed in Jazf1 KO mice. A recent study showed decreased GSIS in beta cell-specific Jazf1 KO mice under hyperglycemic condition ( 16 ) and in beta cells differentiated from Jazf1 KO ( 17 ). Thus, we tested whether TR4 expression or insulin secretion was affected in our animals.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study generated a pancreatic β cell-specific Jazf1 knockout (KO) mouse, which had no discernible phenotype under basal conditions and decreases in glucose-stimulated insulin secretion (GSIS) under hyperglycemic challenged conditions ( 16 ). In contrast, others reported that mice heterozygous for a loss of function mutation had impaired insulin secretion ( 17 ). Although these studies suggest an association between JAZF1 and T2D, the causal relationship between JAZF1 and both T2D and height is still debated.…”
mentioning
confidence: 99%
“…Consequently, JAZF1 overexpressing animals are protected against diet-induced insulin resistance and related metabolic dysfunctions (Jang et al, 2014;Li et al, 2014;Yuan et al, 2015;Wei et al, 2018;Zhou et al, 2020). Furthermore, JAZF1 has been linked to other equally important, metabolically relevant processes, including pancreatic beta cell differentiation and function (Taneera et al, 2012;Kobiita et al, 2020;Park et al, 2021), ribosome biogenesis (Kobiita et al, 2020;Procida et al, 2021) and adipogenesis (Ming et al, 2014a;Jeong et al, 2021).…”
Section: Frontiers In Cell and Developmental Biology Frontiersinorgmentioning
confidence: 99%
“…Furthermore, JAZF1 is expressed in both human (3,4) and mouse b-cells (5,6). JAZF1 is an important regulator of endoplasmic reticulum (ER) stress and ribosome biogenesis via a feedback action preventing the activation of ER and p53 stress-mediated b-cell apoptosis (7), which plays a pivotal role in the differentiation of b-cells and glucose homeostasis (8). Obesity (9) and diabetes status (10,11) alter the JAZF1 expression pattern.…”
Section: Introductionmentioning
confidence: 99%